2018
DOI: 10.26717/bjstr.2018.04.0001022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Papaverine on the Flow of Left Internal Thoracic (Mammary) Artery for Coronary Artery Bypass Grafting

Abstract: LITA arise from their respective subclavian artery. LITA/LIMA in coronary artery bypass grafting associated with approximately 90% long-term graft patency, improved flow rate and lower mortality and morbidity rate.Spasms can occur during CABG surgery, both during harvesting and after the grafting causes early myocardial ischemia and often reduces early graft flow, which could cause perioperative morbidity and even death in high-risk patients [5]. that may be minimized by the local action of vasodilatory agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…ITA use is especially of value in diabetic patients due to reduced incidence of postoperative cardiac events. [1][2][3][4][11][12][13][14][15][16][17] ITA is a branch of subclavian artery. ITA has more nutrient supply to its wall, quick removal of metabolites, production of prostacyclin and nitric acid from its wall all play a role in reducing the incidence of adverse cardiac effects.…”
Section: Discussionmentioning
confidence: 99%
“…ITA use is especially of value in diabetic patients due to reduced incidence of postoperative cardiac events. [1][2][3][4][11][12][13][14][15][16][17] ITA is a branch of subclavian artery. ITA has more nutrient supply to its wall, quick removal of metabolites, production of prostacyclin and nitric acid from its wall all play a role in reducing the incidence of adverse cardiac effects.…”
Section: Discussionmentioning
confidence: 99%
“…Dregelid et al 13 revealed that an intraluminal injection of a papaverine solution and external papaverine exposure provide a greater blood flow rate and distal dilation but at a significant risk of mechanical wall injury. Siddiqeh 14 demonstrated that papaverine was a safe and effective vasodilator for raising the mean blood flow of the LIMA/left internal thoracic artery (LITA) for CABG. Koramaz et al 15 demonstrated that papaverine increased the flow rates of the grafts 30 minutes after papaverine injection.…”
Section: Effect Of Papaverine On Blood Flow and Spasm Of The Imamentioning
confidence: 99%